Incidence of and risk factors for involvement of the central nervous system in acute myeloid leukemia - Uri Rozovski; Maro Ohanian; Farhad Ravandi; Guillermo Garcia‐Manero; Stefan Faderl; Sherry Pierce; Jorge E. Cortés; Zeev Estrov (2014)
It is thought that the low incidence of central nervous system (CNS) involvement in acute myeloid leukemia (AML) does not justify routine CNS prophylaxis, as high-dose cytarabine eliminates CNS disease. To investigate whether chemotherapy that does not include high-dose cytarabine increases the risk of CNS involvement, the medical records of 1412 newly diagnosed patients with AML were reviewed. In 1370 patients, lumbar puncture (LP) was performed only if clinically indicated, and CNS disease was detected in 45 (3.3%) patients. Another 42 patients underwent routine LP as part of an investigational protocol, and in eight (19%) CNS disease was detected (p < 0.0001). Risk factors included high lactate dehydrogenase, African-American ethnicity and young age. Patients receiving high-dose cytarabine and those who did not had similar rates of CNS involvement. Disease-free survival (DFS) and overall survival were shorter in patients with CNS involvement. It remains to be determined whether routine CNS prophylaxis would improve DFS.